1962
DOI: 10.1126/science.138.3547.1328
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Biologic Individuality of the Genetic Dictionary

Abstract: Deoxyribonucleic acid contains sequences complementary to homologous amino-acid transfer ribonucleic acid molecules which serve as the translating device between polyribonucleotides and proteins. This implies that the RNA molecules have their primary origin in DNA. From the amount of DNA participating, one would infer that more than 20 complementary sequences exist per genome, a conclusion consistent with a degenerate code. The fact that complex formation occurs most readily with homologous RNA suggests that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…The saturation level for Arthrobacter crjlstallopoietes tRNA 0.02 %, is close to the value of 0.024 % reported for Escherichia coli (Giacomoni & Spiegelman, 1962). Presumably, 0.35 to 1.5 % of the DNA genome accounts for both the transfer and ribosomal genes as it does in other organisms (Giacomoni & Spiegelman, 1962;Attardi, Huang & Kabat, 1965;Oishi & Sueoka, 1965).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The saturation level for Arthrobacter crjlstallopoietes tRNA 0.02 %, is close to the value of 0.024 % reported for Escherichia coli (Giacomoni & Spiegelman, 1962). Presumably, 0.35 to 1.5 % of the DNA genome accounts for both the transfer and ribosomal genes as it does in other organisms (Giacomoni & Spiegelman, 1962;Attardi, Huang & Kabat, 1965;Oishi & Sueoka, 1965).…”
Section: Discussionsupporting
confidence: 73%
“…Presumably, 0.35 to 1.5 % of the DNA genome accounts for both the transfer and ribosomal genes as it does in other organisms (Giacomoni & Spiegelman, 1962;Attardi, Huang & Kabat, 1965;Oishi & Sueoka, 1965). Table I shows that the major concentration component of the mixed RNA saturated to a level somewhat above this, ranging from 0.65 to 1-06 %.…”
Section: Discussionmentioning
confidence: 91%
“…Since all RNA synthesis in normal cells is presumed to be DNA-dependent (35)(36)(37)(38), it is of particular interest to speculate upon the nature and possible means of identifying the RNA involved in rhythmicity. The evident necessity for a "daily synthesis" of RNA suggests that at least a part of the RNA involved is relatively short-lived, analogous in this regard to the messenger RNA described for other systems (39,40) which functions in protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…23 By 1963 some of their many achievements were presented at Cold Spring Harbor Symposia on Quantitative Biology . For example, proving the universality of the information transfer process in bacteria (Hayashi & Spiegelman, 1961); showing that ribosomal RNA is copied from host DNA (Yankofsky & Spiegelman, 1962), as is soluble RNA (transfer RNA) (Giacomoni & Spiegelman, 1962) 24 . Spiegelman and collegues also showed that within the cell, RNA messages are transcribed from one DNA strand only Hayashi, Spiegelman, Franklin, Luria, 1963).…”
Section: Hybridization As a Scientific Commonsmentioning
confidence: 99%